2021
DOI: 10.3389/fpsyg.2021.697726
|View full text |Cite
|
Sign up to set email alerts
|

The State of Music Therapy Studies in the Past 20 Years: A Bibliometric Analysis

Abstract: Purpose: Music therapy is increasingly being used to address physical, emotional, cognitive, and social needs of individuals. However, publications on the global trends of music therapy using bibliometric analysis are rare. The study aimed to use the CiteSpace software to provide global scientific research about music therapy from 2000 to 2019.Methods: Publications between 2000 and 2019 related to music therapy were searched from the Web of Science (WoS) database. The CiteSpace V software was used to perform c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
2
24
0
2
Order By: Relevance
“…In the case of Frontiers in Psychology, although it is not specific to this area of research, it does belong to the field of psychology, one of the two domains identified in the present study as being main domains. This result is also similar to that of Li et al (2021), mentioned above, where the authors found that the leading journals in the field were specialized in music therapy and where one of the main domains was also psychology.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the case of Frontiers in Psychology, although it is not specific to this area of research, it does belong to the field of psychology, one of the two domains identified in the present study as being main domains. This result is also similar to that of Li et al (2021), mentioned above, where the authors found that the leading journals in the field were specialized in music therapy and where one of the main domains was also psychology.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the geographical distribution of the publications, the results of the study are equivalent to those of a bibliometric study that analyzed the last 20 years of publications on music therapy (Li et al, 2021) since the 10 countries or regions that these authors identified as the main ones are among the twenty top producing countries in art therapy, with the United States heading the list in both cases. The aim of this study was to determine whether the improvement in depression, anxiety, or fatigue during chemotherapy after an anthroposophic art therapy intervention was sufficient to warrant a controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…By the end of 2020, the top keywords were “postherpetic neuralgia” (2002–2009), “gabapentin” (2005–2012), and “double-blind” (2004–2011). The research frontiers can be indicated by an in-depth analysis of these keywords (Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…By the end of 2020, the top keywords were ''postherpetic neuralgia '' (2002-2009), ''gabapentin '' (2005-2012), and ''double-blind'' (2004-2011). The research frontiers can be indicated by an in-depth analysis of these keywords (Li et al, 2021). a. Postherpetic neuralgia: Postherpetic neuralgia is a type of NP that is common among older patients after the rash of singles disappears (Pei et al, 2019b).…”
Section: Research Focuses On Np Combined With Depression or Anxietymentioning
confidence: 99%
See 1 more Smart Citation